Anti-Neoplastic Activity of Litchi chinensis Leaf Extract Against Ehrlich's Ascites Carcinoma in Mice. Issue 1 (2nd January 2016) - Roy, Soma; Banerjee, Bisweswar; Vedasiromoni, Joseph R.
Abstract : The anti-carcinogenic activity of Litchi chinensis leaf extract (LCLE) was investigated against Ehrlich's ascites carcinoma (EAC) in mice. LCLE inhibited the growth and metabolic activity of viable EAC cells in both in vivo and in vitro studies. Treatment with LCLE showed characteristic features of apoptosis. Flow cytometric analysis showed appreciable number of cells in early and late apoptotic stages. LCLE arrested the EAC cell populations in the G2 -M phase of cell cycle. LCLE induced apoptosis was found to be mediated through mitochondrial intrinsic pathway involving the release of cytochrome c into the cytosol and activation of caspase-9 and caspase-3.